2014
DOI: 10.1155/2014/578168
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Conduction Mechanisms in Dielectric Films

Abstract: The conduction mechanisms in dielectric films are crucial to the successful applications of dielectric materials. There are two types of conduction mechanisms in dielectric films, that is, electrode-limited conduction mechanism and bulk-limited conduction mechanism. The electrode-limited conduction mechanism depends on the electrical properties at the electrode-dielectric interface. Based on this type of conduction mechanism, the physical properties of the barrier height at the electrode-dielectric interface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
738
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 999 publications
(776 citation statements)
references
References 24 publications
30
738
1
7
Order By: Relevance
“…To understand the sandwich-structured nanocomposites with different layer arrangements, it is informative to investigate the conduction mechanisms of its components, i.e., c-BCB/BNNS and c-BCB/BT, under elevated temperatures. Several conduction mechanisms exist in polymeric materials, including the hopping conduction, the Schottky charge injection (thermionic emission) and the PooleFrenkel (P-F) emission (20,25). Hopping conduction is commonly observed in amorphous polymers such as c-BCB, as we previously demonstrated (8).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…To understand the sandwich-structured nanocomposites with different layer arrangements, it is informative to investigate the conduction mechanisms of its components, i.e., c-BCB/BNNS and c-BCB/BT, under elevated temperatures. Several conduction mechanisms exist in polymeric materials, including the hopping conduction, the Schottky charge injection (thermionic emission) and the PooleFrenkel (P-F) emission (20,25). Hopping conduction is commonly observed in amorphous polymers such as c-BCB, as we previously demonstrated (8).…”
Section: Discussionmentioning
confidence: 73%
“…1B). It is important to note that the low-field room temperature dielectric loss is drastically different from the loss shown at high electric fields and elevated temperatures because of the nonlinear conduction related to charge injection and leakage current (20)(21)(22)(23). Indeed, at 150°C and 200 MV m −1 , the dielectric loss rises rapidly from 18% of the pristine c-BCB to more than 47% of c-BCB/BT as determined from the electric displacementelectric field (D-E) loops (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that within this region, the injected electrons are partly captured by the traps in the films, while others contribute to the total current [28,29]. Comparing with the first cycle, the I-V curve of the subsequent switching is featured by only two regions which corresponds well with the trap-free SCLC model [30]. The absence of this region in the subsequent switching implies that traps in the films have been filled during the pristine SET process.…”
Section: Zno Resistive Switching Memorymentioning
confidence: 76%
“…This type of thermionic emission is one of the most often observed conduction mechanism in oxide especially in relative high temperature [71]. The current density JSE can be related to electric field (E) and temperature (T) by the Schottky equation as shown in Equation (1).…”
Section: Schottky Emissionmentioning
confidence: 99%